Nanozymatic magnetic nanomixers for enzyme immobilization and multiplexed detection of metabolic disease biomarkers - Li, Di (2023)
Nanozymes with enzyme-mimicking catalytic activity and unique functions have stimulated increasing interest in the biosensing field. Herein, we report a magnetic nanozyme (MNE) with integrated superior peroxidase-like activity and efficient mixing ability. This nanozymatic magnetic nanomixer is synthesized by depositing a Fe2+-doped polydopamine coating on the surface of well-aligned magnetic nanoparticles to form a rigid chain-like nanostructure. Polydopamine coating of the nanozymatic MNE allows for efficient immobilization of natural enzymes such as glucose oxidase, cholesterol oxidase or urate oxidase to produce a series of enzymes-immobilized MNE (MNE@enzymes) with intrinsic multienzyme cascade properties. These MNE@enzymes show synchronously rotating capability in spinning magnetic fields, which leads to an 80∼100% improvement in their overall catalytic efficiencies. In the on-chip detection of small molecular metabolites (i.e., glucose, cholesterol, and uric acid), the rotating MNE@enzymes lead to detection sensitivities 2.1∼4.3 times higher than those of the static ones. Importantly, the consistent performance of the rotating MNE@enzymes offers the possibility of integrating the detection of glucose, free cholesterol and uric acid into a single multiplexing microchip assay with smartphone readout, affording an improved sensitivity, good selectivity and reliability. The designed enzymes-loaded MNEs holds great promise in developing rapid and ultrasensitive measurements of diverse targets of healthcare concerns using portable devices.